Efficacy of phenobarbital is maintained after exposure to mild‐to‐moderate seizures in neonates - Cynthia Sharpe; Charlotte‐Rose Rennie‐Younger; Dug Yeo Han; Suzanne L. Davis; Mark Nespeca; Francesco Pisani; Jeffrey J. Gold; Gail E. Reiner; Sonya Wang; Richard H. Haas (Epilepsia Open)
Abstract To study the relationship between the delay in treatment and the efficacy of phenobarbital in neonates, we re‐analyzed data from the NEOLEV2 study. Continuous video EEG (cEEG) from patients treated with phenobarbital was reviewed by neurophysiologists who marked each seizure. The time from seizure onset to phenobarbital, total seizure burden pre‐phenobarbital, and maximum seizure density (summed seizure burden per hour) pre‐phenobarbital were calculated and correlated with phenobarbital efficacy at 20 mg/kg and at 40 mg/kg. The time between seizure onset and phenobarbital treatment did not predict refractoriness to phenobarbital. However, the maximum seizure density per hour and total seizure burden before phenobarbital treatment were strongly correlated with efficacy. ROC curve analysis showed cut‐offs of maximum seizure density pre‐phenobarbital of 10 ½ min/h and total seizure burden pre‐phenobarbital of 36 ¼ min had excellent discriminatory ability in separating patients in whom phenobarbital would be effective from patients in whom it would not be effective (AUC 0.84, p = 0.0002 and AUC 0.85, p = 0.0051). These data suggest that whereas neonates with high seizure density must be treated as an emergency, mild‐to‐moderate seizures remain responsive to phenobarbital if treated within a time frame of several hours. Plain Language Summary Phenobarbital is very effective at stopping seizures in newborns. But if phenobarbital is given after many hours of seizures, it becomes less effective. We do not know how quickly this happens. Our study found that it does not happen over the short term (<4 h). It is more difficult to stop seizures that cumulatively last more than 10 min/h.